Ophiolite complex of Piedmont-Ligurian basin (Northern Apennines) - Yegorova, T.; Murovskaya, A. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2023)
The Northern Apennines contain remnants of the Piedmont-Ligurian Basin (PLB) or ocean, which during the Late Mesozoic time (mainly in the Jurassic) separated the paleo-Europe (Iberian plate) from the southern paleocontinent Adria at the Africa promontory. The closure of the PLB and subsequent collision of Europe/Adria in Cretaceous-Cenozoic time led to the exhumation of the ophiolite complex of Northern Apennines in the Ligurian units. The paper gives information obtained by the authors during several field trips on the composition of the ophiolite complex of the Northern Apennines, representative of the composition and structure of the oceanic lithosphere. The latter, absent in the territory of Ukraine, is a key question to understanding the evolution of the oceanic crust, subduction processes, and formation of accretion wedges in the transitional zones to the continents. The Ligurian ophiolites of the PLB constitute an accessible and unique window to track the opening and evolution of the slow-spreading oceanic lithosphere. The Internal Ligurian ophiolites consist of km-scale gabbroic bodies intruded into depleted mantle peridotites and bear remarkable structural and compositional similarities to oceanic lithosphere from slow and ultra-slow spreading ridges. The External Ligurian ophiolites, associated with continental crust material and transition zone between the oceanic and continental crust, include mantle sequences retaining a subcontinental lithospheric origin. The gabbro-peridotite associations from the Internal Ligurian ophiolites were explored in the Bracco-Levanto ophiolite massif, which includes a km-scale gabbroic body, recalling the oceanic core complexes from modern spreading centres, intruded into the mantle peridotites. The peridotites and the gabbros from these ophiolites record a composite history involving deformation and alteration from high temperature to seafloor conditions. The top of the peridotites is covered by tectono-hydrothermal breccias (ophicalcites), radiolarites, and sedimentary breccias that testify to the exposure of peridotites at the seafloor. This succession is then covered by basalts pillow-lavas. Thus, the almost full section of the ophiolite complex is represented here.